2007
DOI: 10.1158/0008-5472.can-06-2763
|View full text |Cite
|
Sign up to set email alerts
|

Shared MHC Class II–Dependent Melanoma Ribosomal Protein L8 Identified by Phage Display

Abstract: Antigens recognized by T helper (Th) cells in the context of MHC class II molecules have vaccine potential against cancer and infectious agents. We have described previously a melanoma patient's HLA-DR7-restricted Th cell clone recognizing an antigen, which is shared among melanoma and glioma cells derived from various patients. Here, this antigen was cloned using a novel antigen phage display approach. The antigen was identified as the ribosomal protein L8 (RPL8). A peptide of RPL8 significantly stimulated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…41 The RPL8 antigen may represent a relevant vaccine target for patients with melanoma, glioma and breast carcinoma whose tumors express this protein. 42 Over-expression of RPL8 has never been reported in osteosarcoma though it maps in a region frequently altered in this tumor. CGH studies have previously shown frequent gain of 8q region with controversial results as to its prognostic value.…”
Section: Discussionmentioning
confidence: 94%
“…41 The RPL8 antigen may represent a relevant vaccine target for patients with melanoma, glioma and breast carcinoma whose tumors express this protein. 42 Over-expression of RPL8 has never been reported in osteosarcoma though it maps in a region frequently altered in this tumor. CGH studies have previously shown frequent gain of 8q region with controversial results as to its prognostic value.…”
Section: Discussionmentioning
confidence: 94%
“…The most critical genes affected by these amplifications are RPL8, reportedly up-regulated in different cancers (e.g. HCC, melanoma, glioma and breast carcinoma 24,25 ) and MLLT4 , described to generate a fusion oncogene together with AF6 inducing leukemic transformation 26 . In terms of focal deletions, these ones affect 31% of cases, being the most common at 19p13.2 locus (containing STK11, a TSG serine/threonine-protein kinase that regulates mTOR signaling), at 19p13.12 (covering LPHN , with a protective role in non-small cell lung cancer 27 ) and at 22q13.32, described as a candidate TSG locus in other tumors 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RPL3 and RPL8 were identified as dysregulated ribosomal associated proteins of U87 cells. RPL8, a component of the 60S subunit of ribosome, is involved in protein synthesis and RPL8 antigen may represent a relevant vaccine target for patients with glioma [ 21 ]. Besides, the restoration of RPL3 protein may resensitize the resistant cells to the drug by regulating the reactive oxygen species (ROS) levels in lung cancer cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%